The use and inter-relationship of compound resin and glass ionomer cement (GIC) in sandwich restorations (Research, Society and Development, 2021)
Introduction: The sandwich technique is a procedure that combines the glass ionomer cement (GIC) with the composite resin (CR) in order to obtain the best physical-mechanical and aesthetic properties of each one. Objective: perform a literary review on the use of this method in direct restorations and analyze how the interaction between the two materials occurs. Methods: A search of the literature published between 2010 and 2021 was carried out in the databases PubMed/ Medline, SciELO, Lilacs and Google Scholar, using pre-selected descriptors. 40 studies were included that met the inclusion and exclusion criteria. Results: The association of GIC with CR brings to the direct restoration the benefits of pulp protection, anti-cariogenic effect, less polymerization contraction, greater retention and better aesthetic properties. This method can be classified as open, closed, mediate and immediate, these variations will depend, respectively, on the indication and the form of preparation of the procedure. Conclusion: When carrying out the acid conditioning of the surface of the conventional GIC, it is necessary to be cautious, since the differences in the setting reactions of this material and the CR can interfere with the final properties of the restoration. However, resin-modified glass ionomer cement does not require this procedure. Although some scholars do not suggest this type of pre-treatment, due to the possibility of promoting cracks and decreasing its strength, research claims that the mixed technique can be performed effectively when using both conventional and self-etching adhesive systems, as no were observed significant differences bond strength when comparing them.